(untitled) (Journal of Philosophy Culture and Political Science, 2018)
Everyone is familiar with the fact that for a society in which a particular religion only began to emerge and for the society in which religious views reached its heights, presentation to the path of religion and ways to strengthen Sharia law will not be the same. Excellent wisdom and absolute knowledge of the Creator encompassing all things, in cases of necessity some sharia rules might be changed from previous sharia norms to benefi t mankind. This phenomenon is known in the Shari’ah on the terms «Nasikh» and «mansukh». This article discusses the theory of «Nasikh» in the writings of the famous medieval theologian , a lawyer and linguist of Kazakh steppes Husamuddin al-Siganak and issues of Nasikh legal norms in religious texts on the transformation of society and time. Key words: Husamuddin as-Sygnaki, islam, nasikh, mansukh, law, religious text.